Human rights and their philosophical enemies - Bertomeu, María Julia (Estudios de Filosofía, 2008)
After a century and a half of eclipse (1795-1945), human rights reappeared after the end of World War II. Not only in the Constitution of the IV French Republic and in the Preamble to the Constitution of the II German Republic; they were the subject of nothing less than a solemn international declaration in 1948 by the United Nations Assembly. Two philosophical questions are of interest in this intervention: 1. What the philosophical idea of ​​law, if there is any homogeneous one that unites them, has the supporters of human rights and citizens. And conversely, what idea of ​​law, if there is one that also integrates them, do the philosophical enemies of human rights have. 2. If, it seems, the philosophical defenders of human rights are always unequivocal supporters of ethical universalism, the interesting philosophical question naturally arises as to the historically particular origin of an ideology or an intellectual program that claims to be universal, that is that is to say, that it intends to normatively transcend the concrete historical contexts that engendered it. [Fragment]